Compromise and utopia_ an interrupted intent of the modern endeavour - Casal Ribeiro, Helder (2016)
The present essay is part of a research on the design process between the 1940s and 1960s, an experimental period in the portuguese modern architectural scene, that in the attempt to construct a renovated discourse, incorporates and reformulates the principles defended by the modern movement, transforming a potentially anachronistic moment - a consequence of sociocultural asymmetry with international context - in a foundational period for Portuguese contemporary architecture, whereby we can enhance themes specific to SAAL's process. The purpose is to pursue a narrative that seeks to formulate an updated and prepositional response to the problems of our time - how to integrate, through the discourse of compromise, the premises and heritage of modern architecture, in response to mundane circumstances, without losing its transformative and inspiring condition for a new future. We aim to overlap the design process of São Victor SAAL, 1974/77, Alvaro Siza and Edifício do OURO, 1951/55, Mário Bonito, given the dichotomous relationship between authorship (extraordinary architecture) and social activism (architecture and power), emphasizing the social dimension needed to respond to the pressing issues of today's society.